2008
DOI: 10.1103/physrevb.78.174420
|View full text |Cite
|
Sign up to set email alerts
|

Spatially anisotropic Heisenberg kagome antiferromagnet

Abstract: We study the quasi-one-dimensional limit of the spin-1/2 quantum Heisenberg antiferromagnet on the kagome lattice. The lattice is divided into antiferromagnetic spin chains ͑exchange J͒ that are weakly coupled via intermediate "dangling" spins ͑exchange JЈ͒. Using one-dimensional bosonization, renormalization-group methods, and current algebra techniques, the ground state is determined in the limit JЈ Ӷ J. We find that the dangling spins and chain spins form a spiral with O͑1͒ and O͑JЈ / J͒ static moments, res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
850
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 492 publications
(859 citation statements)
references
References 63 publications
8
850
0
1
Order By: Relevance
“…This is convenient for the application of periodic boundary conditions in the TST. Many previous works on the anisotropic triangular lattice in two dimensions, including those by some of the authors 11,13 , use instead "cartesian" coordinates, as shown in in Fig. 1a.…”
Section: Model and Dmrg Methods A Hamiltonian And Notationmentioning
confidence: 99%
See 3 more Smart Citations
“…This is convenient for the application of periodic boundary conditions in the TST. Many previous works on the anisotropic triangular lattice in two dimensions, including those by some of the authors 11,13 , use instead "cartesian" coordinates, as shown in in Fig. 1a.…”
Section: Model and Dmrg Methods A Hamiltonian And Notationmentioning
confidence: 99%
“…The uniform magnetization has scaling dimension 1, whereas both the staggered spin magnetization and the staggered dimerization have scaling dimension 1/2. These three continuum operators form a closed operator algebra with well-defined operator product expansions (OPEs) used widely in literature [11][12][13][74][75][76][77] . For instance, the product of J R and N can be expanded as…”
Section: ≥ 2: Mean-field Transitionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] . For systems with imperfect Kagomé structure, magnetic anisotropy induced by Dzyaloshinsky-Moriya (DM) interaction [5] , spatially anisotropic exchange [6] , and/or interlayer coupling may reduce geometry frustration and lead to antiferromagnetic ordering with very low Né el temperatures.…”
mentioning
confidence: 99%